1998
DOI: 10.1097/00000542-199806000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Desflurane Increases Pulmonary Alveolar-Capillary Membrane Permeability after Aortic Occlusion-Reperfusion in Rabbits 

Abstract: Desflurane anesthesia increased xanthine oxidase-dependent alveolar-capillary membrane compromise after aortic occlusion-reperfusion in concert with depletion of a key tissue antioxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Nonpulmonary I/R: the nonpulmonary I/R model has been used mainly in rats and mice, although there are some studies in rabbits (8,150) and sheep (116,195). Models differ in terms of the anatomic area subjected to ischemia, e.g., gut, liver, kidneys, lower torso, the duration of the ischemic period, and the duration of reperfusion.…”
Section: Models Targeting the Epithelium And Endotheliummentioning
confidence: 99%
“…Nonpulmonary I/R: the nonpulmonary I/R model has been used mainly in rats and mice, although there are some studies in rabbits (8,150) and sheep (116,195). Models differ in terms of the anatomic area subjected to ischemia, e.g., gut, liver, kidneys, lower torso, the duration of the ischemic period, and the duration of reperfusion.…”
Section: Models Targeting the Epithelium And Endotheliummentioning
confidence: 99%
“…At the completion of this experiment, the BALF concentration of LDH in the DES-IR group was higher than in the other groups. This indicated not only the decreased functions of the vascular endothelium, but also damage to lung tissue (Nielsen et al 1998). …”
Section: Discussionmentioning
confidence: 99%
“…Desflurane has a chemical formula similar to that of isoflurane (Eger 1987), but it has more potent stimulatory effects on the sympathetic nerve than isoflurane (Weiskopf et al 1994). In addition, the blocked thoracic aorta causes oxidative stress in the entire organism through ischemia and subsequently pulmonary vascular permeability, which is exacerbated by desflurane (Nielsen et al 1998). In addition, in pigs under mechanical ventilation, desflurane (1 minimum alveolar concentration [MAC]) inhalation caused oxidative stress in the lungs and induced the apoptosis of lung cells (Allaouchiche et al 2001; Kalimeris et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical and experimental studies also demonstrated that hepatoenteric ischemiareperfusion caused significant pulmonary injuries (2,5,(33)(34)(35)(36). Activation of neutrophils and their sequestration and adherence to the pulmonary endothelium are important steps in the development of a pulmonary microvascular permeability increase.…”
Section: Discussionmentioning
confidence: 99%